Biomarkers in biological fluids in adults with periodontitis and/or obesity: A meta-analysis - Renata Scheeren Brum; Poliana Mendes Duarte; Graziela De Luca Canto; Carlos Flores-Mir; César Augusto Magalhães Benfatti; André Luís Porporatti; Gláucia Santos Zimmermann (Wolters Kluwer Medknow Publications, 2020)
Obesity and periodontal diseases have been investigated to be interconnected, but the molecular mechanism underlying this association is still not clear. The aim of this systematic review is to assess the association of serum, salivary and gingival crevicular fluid (GCF) inflammatory markers (IMs), obesity, and periodontitis. Studies that evaluated IM of adults according to obesity status (O) and periodontitis status (P) (O+P+; O-P+; O+P-) were screened on several electronic databases and grey literature up until February 2019. Risk of bias assessment and level of evidence were evaluated through Fowkes and Fulton scale and Grading of Recommendations Assessment, Development and Evaluation (GRADE). Meta-analyses were grouped according to the biological matrix studied (serum/GCF) and groups (O+P+ vs. O−P+/O+P+ vs. O+P−). Out of the 832 studies screened, 21 were considered in qualitative synthesis and 15 in quantitative synthesis (meta-analysis). Although included studies showed mostly "no" or "minor" problems during the quality assessment, GRADE assessment indicated very low to moderate level of evidence based on the question answered. O+P+ adults exhibited significantly higher serum levels of C-reactive protein (CRP), interleukin 6 (IL-6), leptin, and tumor necrosis factor-α (TNF-alpha) and higher resistin GCF levels than O−P+. O+P+ adults showed significantly higher serum levels of IL-6 and leptin and lower adiponectin serum levels than O+P−. Only qualitative information could be obtained of the IM vaspin, omentin-1, chemerin, IL-10, progranulin, MCP-4, IL-1β, and interferon-γ (IFN-γ). Obesity and periodontitis, together or separately, are associated with altered serum and GCF levels of CRP, IL-6, leptin, TNF-alpha, adiponectin, and resistin. It was not possible to evaluate the association between obesity and periodontitis at salivary levels. The role of recently investigated biomarkers as vaspin, omentin-1, chemerin, IL-10, progranulin, MCP-4, IL-1β, and IFN-γ, which can be key points underlying the association between obesity and periodontitis, remains to be further investigated.